We're in This Together: Intergenerational Health Policies as an Emerging Public Health Necessity - Plagg, Barbara; Oschmann, Jörg; Engl, Adolf; Piccoliori, Giuliano; Conca, Andreas; Eisendle, Klaus (Frontiers in Human Dynamics, 2020)
The global handling of the COVID-19 pandemic illustrates that most governments are lacking intergenerational public health solutions. Discontinuity of health care services, mental and physical burden of isolation and school closures increase various pathologies and may provoke long-term health damage amongst the youngest. Unbalanced generational approaches within health policies have been evident before the pandemic and will continue to be a global challenge as both acute and chronic threats due to environmental hazards and social disparities are increasing. Beyond the current crisis and in dealing with any public health threat, intergenerational approaches focused on the welfare of children and adolescents and the long-term impact on their lives are imperative and must be a core part in the development and implementation of public health policies.